THE DESCRIPTION OF THE PERSONALITY OF AMIR TIMUR AND THE INTERPRETATION OF HIS MILITARY CAMPAIGNS IN GERMAN HISTORIOGRAPHY IN THE FIRST HALF OF THE 15TH-17TH CENTURIES. (Scientific journal of the Fergana State University, 2025)
The article examines how the personality of Amir Timur was interpreted in German historiography during the 15th-16th centuries, as well as the territories he conquered. The article also discusses how German historiography developed during the 15th-17th centuries, the methods used to present history, the development of humanistic ideas in Germany, and the extent to which the Reformation influenced German historiography. The article includes information from the Travels of the German knight Johann Schiltberger, as well as the works of early national German historians such as Hartmann Schedel, Sebastian Brandt, and Leonhard Fuchsberger, who provided details about the personality of Amir Timur and how he achieved global power. It is also noted that humanistic ideas developed later in Germany compared to other European countries, and the strong influence of the Catholic Church on German science. Furthermore, Germany's division into many small principalities, leading to territorial conflicts between them, also impacted historiography. As a result, intellectual circles in Germany were almost entirely cut off from the outside world. The article highlights that Schiltberger, through his notes, Turkish sources, and French historians, acquired information about Amir Timur’s personality and his political activities. In the first half of the 15th-17th centuries, German historians studied the personality of Amir Timur, not relying on analytical data but presenting it in the form of chronicles and narrative stories.